Mental health of multiple victimized immigrant women in Portugal: Does resilience make a difference? - Gonçalves, Mariana (2020)
Multiple victimization and their impact on the mental health of immigrant women have been understudied. This paper assesses the relationship between multiple victimization and the emotional maladjustment of immigrant women in Portugal. Data were collected from a sample of 107 immigrant women via a set of questionnaires that assessed the victimization experience, psychological maladjustment, and resilience. The main objective was to analyze the role of resilience in the mental health of multiple victimized immigrant women in Portugal. The results showed that 78.5% of immigrant women in Portugal reported experiencing at least one type of victimization during life (66.4% experienced multiple victimization and 12.1% single victimization), 45% displayed psychological maladjustment and 14% suffered from Post-Traumatic Stress Disorder. Unemployment, low socioeconomic status and a higher number of types of victimization experienced constituted risk factors for mental health problems. A mediation model found that there is an indirect effect of the total index of victimization in psychological maladjustment, mediated by resilience. The results suggest a complex relationship between victimization and emotional maladjustment, combining individual, interpersonal, structural and social factors. The implications for practice are discussed, not only regarding the risk intervention, but also the empowerment of immigrant women.